2016
DOI: 10.1007/s11332-016-0319-4
|View full text |Cite
|
Sign up to set email alerts
|

Balance in young male soccer players: dominant versus non-dominant leg

Abstract: Purpose: To investigate whether soccer affects the young players’ one leg stance balance ability and to understand if balance ability in young soccer players is influenced by age, morphometric parameters or motor coordination capabilities. Methods: Ninety-two male healthy pediatric soccer players aged between 5 and 10 years were enrolled in this study. Sway path, sway area, and sway velocity of center of pressure (CoP) were recorded by means of a strain gauge platform with automatic weight correction. Athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…We also recommend that the proportion of foot dominance should be carefully considered, although the foot dominance in selected FPI-6 score showed little differences in current study (Table 1). In previous studies [40][41][42], postural stability were not influenced by dominant side in healthy populations.…”
Section: Postural Stability and Knee Isokinetic Strengthmentioning
confidence: 71%
“…We also recommend that the proportion of foot dominance should be carefully considered, although the foot dominance in selected FPI-6 score showed little differences in current study (Table 1). In previous studies [40][41][42], postural stability were not influenced by dominant side in healthy populations.…”
Section: Postural Stability and Knee Isokinetic Strengthmentioning
confidence: 71%
“…Furthermore, literature suggests no effects of leg dominance on a single limb stance in adolescent and teen populations. Mala et al 36 and Bigoni et al 37 found that limb preference had no significant effect on postural stability during a static single leg stance on a pressure mat among elite teenage soccer players and in pre-pubescent male soccer players, respectively. To date, few studies have used the YBT-LQ to compare limb differences in young adolescent populations.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers considered the SLS as a dynamic, rather than static, balance test [2]. Bigoni, Tarati and Gandolla et al (2017) [28] found lower extremity and the trunk when the whole body was looked as a single unit in an upright posture. However, among the kinematic chain of joints from foot to the head, there are more than two body segments that involve balance maintenance.…”
Section: Discussionmentioning
confidence: 99%